The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1537/asj.114.139
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Variation of Crania of the Medieval Period Japanese

Abstract: This study measured the medieval crania from the Kanto District in Japan and compared the measurements with those of the preceding studies for the purpose of clarifying the morphological variation within several medieval populations in the Kanto District and between populations from the Kanto and northern Kyushu-Yamaguchi Districts. The materials utilized in this study consist of human skeletal remains from the Yuigahama-minami (individual burials), Chusei-Shudan-Bochi, Gokurakuji sites in the Kamakura city, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…Subsequently, a similar tendency has been shown with medieval samples newly unearthed in the Kanto region and in western Japan (e.g. Nakahashi and Nagai, 1985;Sakuma, 1986;Nakahashi, 1993;Matsushita, 2002;Nagaoka et al, 2006). Thus, strong alveolar prognathism is generally accepted as one of the common characteristics of medieval people in mainland Japan.…”
Section: Introductionsupporting
confidence: 63%
“…Subsequently, a similar tendency has been shown with medieval samples newly unearthed in the Kanto region and in western Japan (e.g. Nakahashi and Nagai, 1985;Sakuma, 1986;Nakahashi, 1993;Matsushita, 2002;Nagaoka et al, 2006). Thus, strong alveolar prognathism is generally accepted as one of the common characteristics of medieval people in mainland Japan.…”
Section: Introductionsupporting
confidence: 63%
“…Although Suzuki (1956) and subsequent studies have emphasized this peculiarity, virtually no attention has been paid to among-site differences in the medieval series. An examination of the variations in cranial metric traits in medieval populations, however, showed that the Zaimokuza series had more dolichocephalic and chameprosopic crania than other medieval series (Nagaoka et al, 2006). Nagaoka et al (2006) demonstrated that the peculiarity of the medieval series appeared more strongly in the human skeletons of the Kamakura period than in those of the Muromachi period and that the craniometric variations among them reflected chronological differences.…”
Section: Discussionmentioning
confidence: 95%
“…An examination of the variations in cranial metric traits in medieval populations, however, showed that the Zaimokuza series had more dolichocephalic and chameprosopic crania than other medieval series (Nagaoka et al, 2006). Nagaoka et al (2006) demonstrated that the peculiarity of the medieval series appeared more strongly in the human skeletons of the Kamakura period than in those of the Muromachi period and that the craniometric variations among them reflected chronological differences. This study showed that the YCSB-SI series had a larger upper facial height and smaller nasal breadth than the Zaimokuza series and that the peculiarity appeared more strongly in the human skeletons of the Kamakura period than in those of the Muromachi period.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations